Sosialisasi Cara Sehat Mengelola Keuangan Keluarga Kepada Para Ibu di GKPI Jemaat Khusus Teladan - Loo, Petrus; Situmorang, Irvan Rolyesh; Simarmata, Asiana; Nainggolan, Susan G (Jurnal Masyarakat Indonesia (Jumas), 2023)
Managing finances is one of the things that is difficult to do for some people. This is said to be difficult due to various factors, namely, high needs and wants, as well as incompatibility of income and expenditure. This situation often occurs in families, where the high demands of life must be met. Some financial principles that must be applied in the family easily and simply are spending must be smaller than income, avoiding debt, living simply, managing finances simply, saving, paying bills as soon as possible when getting income and the agreement of family members in managing finances. Finances can be managed properly if there is consistency in the household against the agreement that has been previously set.